2016
DOI: 10.1021/acs.energyfuels.6b01647
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective CO2 Extraction from a Mixture of CO2 and H2 Gases Using Hydroquinone Clathrates

Abstract: The potential of hydroquinone (HQ) clathrates to selectively separate/capture CO2 from mixtures of CO2 and H2 gas is investigated. Selective CO2 enclathration within cages of a HQ framework, from mixtures of various concentrations of the two gases, are identified using 13C nuclear magnetic resonance (NMR) and Raman spectra. Spectroscopic results indicate that CO2 molecules from the gas mixture are exclusively accommodated into the cages of HQ clathrates and that the H2 molecules are thereby concentrated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 28 publications
5
45
1
Order By: Relevance
“…First, for the same thermodynamic conditions and reaction time, the gas storage capacity of the CO 2 HQ clathrates was found to be relatively high, corresponding to an averaged clathrate occupancy of 0.94 ± 0.05 (close to unity). This value is consistent with literature data obtained from gas−solid reactions carried out in comparable experimental conditions: about 0.91−1.0 was found for 7 days' reaction between powdered HQ and CO 2 at 298 K and 3.0 MPa 33 and 0.95 for the reaction between powdered HQ and a CO 2 /H 2 mixture in which the CO 2 had a partial fugacity of at least 1.8 MPa at 298 K. 34 Note that other authors have found lower clathrate occupancy values in different experimental conditions: 0.74 was obtained for 30 h of gas−solid reaction at 293−353 K and at a CO 2 pressure of 4.0 MPa 13 and 0.76 after 45 days of reaction at 323 K and 3.0 MPa. 37 Furthermore, our occupancy result is also higher than what is generally found for CO 2 HQ clathrates formed by crystallization from a solvent.…”
supporting
confidence: 92%
“…First, for the same thermodynamic conditions and reaction time, the gas storage capacity of the CO 2 HQ clathrates was found to be relatively high, corresponding to an averaged clathrate occupancy of 0.94 ± 0.05 (close to unity). This value is consistent with literature data obtained from gas−solid reactions carried out in comparable experimental conditions: about 0.91−1.0 was found for 7 days' reaction between powdered HQ and CO 2 at 298 K and 3.0 MPa 33 and 0.95 for the reaction between powdered HQ and a CO 2 /H 2 mixture in which the CO 2 had a partial fugacity of at least 1.8 MPa at 298 K. 34 Note that other authors have found lower clathrate occupancy values in different experimental conditions: 0.74 was obtained for 30 h of gas−solid reaction at 293−353 K and at a CO 2 pressure of 4.0 MPa 13 and 0.76 after 45 days of reaction at 323 K and 3.0 MPa. 37 Furthermore, our occupancy result is also higher than what is generally found for CO 2 HQ clathrates formed by crystallization from a solvent.…”
supporting
confidence: 92%
“…By contrast, organic gas clathratesin which the host lattices are composed of organic molecules such as hydroxyaromatic compounds 1 have been much less investigated. Besides their ability to fascinate scientists for over a century, these organic inclusion compounds, particularly those formed with hydroquinone (HQ), appear to be promising materials for practical applications such as hydrogen storage, 4 gas separation by selective enclathration, 5,6 and sequestration of dangerous substances. 7 The stable structure of HQ under ambient conditions (αform) can be converted, in certain conditions, into HQ clathrates (β-form) by encaging a variety of suitable guest species such as methanol, acetonitrile, sulfur dioxide, argon, krypton, xenon, and others.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional technologies face some challenges, in addition to their energy consumption and high capital cost. For example, the commercial absorption technology uses a corrosive and environmentally unfriendly absorber, while the membrane technology also has some disadvantages due to its limited thermal stability and low selectivity [8]. In this regard, the need to develop novel and low-cost technologies is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…This organic compound is a solid crystal at room temperature and atmospheric pressure. In addition, because only one kind of cavity is formed when HQ is converted to the clathrate form, the specific gas component having the best fit can be selectively separated from the gas mixture in the solid form [8]. In our previous reports, we published work on selective separation of CO 2 and CO from binary CO 2 + H 2 and CO + H 2 gas mixtures, respectively [8,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation